1971
DOI: 10.1180/minmag.1971.038.296.02
|View full text |Cite
|
Sign up to set email alerts
|

Shape analysis of moldavites and their impact origin

Abstract: SUMMARY. I666 moldavites from 19 localities in Bohemia and 617 moldavites from IO localities in Moravia were measured to yield parameters L (length), B (breadth), and T (thickness). A digital computer was programmed to calculate values T/L, (L--B)/(L--T), andThe data obtained permit an interpretation that localities of moldavites with low average sphericity contain less heated material. Less heated and thus more viscous glass could have flown along shorter trajectories (Bohemia). More heated glass was ejected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1973
1973
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The extremely localized occurrence of moldavites in only one direction from the crater may point to an oblique impact from the west (Schultz and Gault, 1982). Konta (1971) has suggested that the variations between the Moravian and Bohemian Moldavites could be explained by different ejection angles from the Ries crater resulting in different atmospheric heating histories, with the lesser heated material landing in Bohemia (a range of 260 km) and the more heated glass landing in Moravia (a range of 400 km).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The extremely localized occurrence of moldavites in only one direction from the crater may point to an oblique impact from the west (Schultz and Gault, 1982). Konta (1971) has suggested that the variations between the Moravian and Bohemian Moldavites could be explained by different ejection angles from the Ries crater resulting in different atmospheric heating histories, with the lesser heated material landing in Bohemia (a range of 260 km) and the more heated glass landing in Moravia (a range of 400 km).…”
Section: Discussionmentioning
confidence: 99%
“…Moldavites found in different localities have systematic differences in shape and in contents of lechatelierite and bubbles that may represent different degrees of heating (Konta, 1971). Bohemian moldavites at a range of approximately 300 km from the Ries crater, consist mainly of drop-like, flat, or elongated fragments with an average weight of 4.5 gm (Konta, 1971).…”
Section: Moldavitesmentioning
confidence: 99%
See 2 more Smart Citations
“…The amount of lechatelierite depends on the temperature conditions of origin. Higher temperature caused a lower abundance of lechatelierite in Czech and German moldavites (Barnes 1969;Konta 1971a;Lange 1995). Lechatelierite in moldavites is represented by very pure silica (Fig.…”
Section: Referencesmentioning
confidence: 99%